The Relationship between Self-Control and Students' Compliance Behavior on Senior High School: Hubungan antara Kontrol Diri dengan Perilaku Kepatuhan Siswa pada Peraturan Sekolah Menengah Atas - Dita Rahayu; Ghozali Rusyid Affandi (Academia Open, 2022)
The purposeofthispaper is todeterminetherelationshipbetweenself-controlandmeeting the needs of students with school organizations atSMK X Pandaan, where there are problems due to lack of school organization. The population used in this study was 270 while the sample of this study was 152 students who were carried out at SMK X Pandaan. In determining the subject with the stratified random sampling technique, two psychological scales with the Likert scale model were used to collect data in this study, namely the self-control scale of the behavioral scale of compliance with school rules. Data analysis was performed using the statistical test technique of Pearson Flow Moment Correlation. The results of the data analysis of this study indicate that there is a significant positive relationship between self-control and compliance with school rules and the performance of SMK X Pandaan students of 0.37. at a significance level of 0.001 (<0.005). the results of hypothesis testing indicate that the hypothesis can be accepted. The results showed that students' self-control according to school regulations was mostly moderate at SMK X Pandaan. Highlights: The purpose of the study: To determine the relationship between self-control and meeting the needs of students with school organizations at SMK X Pandaan. Sample and data collection: The study included 152 students from a population of 270, using the Likert scale model to measure self-control and compliance with school rules. Findings: There is a significant positive relationship (0.37) between self-control and compliance with school rules among SMK X Pandaan students, indicating the importance of self-control in maintaining school regulations. Keywords: self-control, compliance with school rules, SMK X Pandaan, students, relationship.